Modelling of Dynamic Friction Across Solid Material Interfaces Using Molecular Dynamics Techniques - Epiphaniou, Nicholas (Cranfield University, 2009)
The topic of this PhD is to investigate materials interfaces under the application of com-pressive forces and dynamic friction. Friction studies are important in applications for high-speed machining and ballistic penetration modelling, two areas where it is important to understand the behaviour of rapidly moving interfaces. Gaining insight into the velocity dependence of the effective tangential force, and its time-evolution, under various external loads is also of particular interest. It is important to understand on an atomic and/or molec-ular level the fundamentals of tribological processes. Some of the processes investigated in this thesis include plastic deformation due to high compression, the response of materials when sliding occurs in terms of temperature variation across the interface and its relation-ship with atomic diffusion. Moreover, the materials dependence on operating conditions of temperature, loading and dynamic friction are factors that ultimately determine the design of tribological systems. In the last few years it has been shown that materials properties depend on the size, as smaller specimens are relatively stronger than larger ones. This thesis is aiming to em-ploy state of the art numerical and theoretical methods, which are vital to give a significant insight and understanding of the fundamental issues concerning dynamic friction of tribo-logical processes at the atomic scale. The mechanical behaviour is investigated in detail to reveal an accurate theoretical description of the frictional force at metallic surfaces. Special consideration is taken into account for the mechanism that causes dissipation in the form of heat. The strong deformation when materials undergo dynamic friction causes energy to dissipate away from the interface at a high rate. Additionally, investigation of the plastic deformation and its variation under conditions prevalent at high speed sliding is carried out. Knowledge of the yield point under these conditions is important to obtain accurate constitutive models for the shear stresses. In-vestigating how the material strength varies under sliding friction and obtaining accurate evaluation of the stresses involved has proved difficult and time consuming. This is primar¬ily attributed to the fact that experiments are difficult to conduct and expensive facilities are required. This thesis focuses on aspects of this complex process with the aid of molecular dynamic simulations.